2016
DOI: 10.3928/01484834-20160114-03
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Senior Nursing Students' Communication Experience With English-Speaking Patients

Abstract: Standardized patient practice emphasized the significance of cultural differences, of knowing and using a foreign language, of communication, and of patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…It has also been reported in the literature that language barriers prevent health professionals from communicating with patients with different cultural backgrounds (Taylor, Nicolle & Maguire, 2013). In a study by Guvenc et al (2016), simulation based education using SPs was considered as an appropriate active education method for coping with language barriers of students . A study by Perry et al (2015) pointed out that e-simulation effective methods that participants are understanding individuals who are language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported in the literature that language barriers prevent health professionals from communicating with patients with different cultural backgrounds (Taylor, Nicolle & Maguire, 2013). In a study by Guvenc et al (2016), simulation based education using SPs was considered as an appropriate active education method for coping with language barriers of students . A study by Perry et al (2015) pointed out that e-simulation effective methods that participants are understanding individuals who are language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…To support verbal communication : Communication has two components, namely, verbal and nonverbal. The differences in the native languages of nurses and patients creates communication barriers [ 53 ]. Moreover, verbal communication and nonverbal communication can conflict with each other in one interaction [ 10 ] and patients believe the nonverbal when verbal communication is incongruent with nonverbal communication [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 27 studies that matched the inclusion criteria were identified. The studies were conducted in five countries: twenty-two in the United States [4][5][6][7]11,12,33,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50], two in Australia [9,51], two in Turkey [52,53], one in Canada [54] and Norway [33]. Among them, one study was a bi-national intervention carried out at both American and Norwegian universities [33].…”
Section: Participants Of Studiesmentioning
confidence: 99%
“…Six studies were conducted on medical students [5,[37][38][39][40]54]. Twelve articles focused on nursing students [6,7,11,12,33,[41][42][43]49,50,52,53]. Three papers presented data on dentistry students [4,35,46], one on pharmacy students [47], and one on physiotherapy students [48].…”
Section: Participants Of Studiesmentioning
confidence: 99%